The Prevalence and Causes of Visual Impairment in Central Sri Lanka : The Kandy Eye Study - EDUSSURIYA, Kapila; SENNANAYAKE, Saman; SENARATNE, Tissa; MARSHALL, Drew; SULLIVAN, Thomas; SELVA, Dinesh; CASSON, Robert J (Ophthalmology (Rochester, Minn.), 2009)
To determine the prevalence and causes of uncorrectable visual impairment in the Kandy District of central Sri Lanka. Population-based, cross-sectional study. Inhabitants >or=40 years of age from villages in the Kandy District were selected by randomized cluster sampling; 1721 eligible participants were identified and 1375 participated in the study. The ophthalmic examination included best-corrected logarithm of the minimum angle of resolution visual acuity (VA), slit-lamp examination of the anterior segment, and dilated stereoscopic fundus examination. The principal cause of visual impairment after best correction was recorded. Visual impairment (better eye <6/18) and blindness (better eye <3/60) after best correction. Comprehensive examinations, including VA, were performed on 1375 subjects (79.9% participation rate). The prevalence of blindness was 1.1% (95% confidence interval [CI], 0.002-0.020; 15 participants). The prevalence of visual impairment was 5.9% (95% CI, 0.043-0.075; 81 subjects). Cataract and age-related macular degeneration were the main causes of visual impairment. Visual impairment remains a major public health problem in central Sri Lanka. Specific programs directed at reducing the cataract burden need to be implemented. The authors have no proprietary or commercial interest in any materials discussed in this article.